Herbicidas hormonales mecanismo de acción - Torres Vasconez, Thalia Sherly (2022)
Hormonal herbicides have the ability to control weeds by affecting their chemical physiological process as they penetrate the interior of the plants and move within them from the site where they penetrated to the site where they exert their action. They are made up of chemical families: Phenoxyacetic Acids, Benzoic Acids and Peridines. Its mechanism of action, which is exerted or produced by controlling the hormonal part of the plant, which triggers several processes in order to generate the death of the plant, there is another mechanism of action that also affects the hormonal part of the plant, what they are pipo auxin herbicides. This work obtained summaries through the analysis technique so that the reader knows the importance of hormonal herbicides action, it was determined that to promote the mechanisms of action, the correct dose must be applied, allowing a group of symptoms such as: the paralysis of growth in root meristems, loss of tropism. As a recommendation when applying herbicides, it should be the correct dose, taking into account climate factors such as wind and temperature.